2018
DOI: 10.1116/1.5035417
|View full text |Cite
|
Sign up to set email alerts
|

Microwave imaging of etching-induced surface impedance modulation of graphene monolayer

Abstract: Impact of processing-induced structural defects on the electrical properties of a graphene monolayer has been investigated using scanning microwave microscopy (SMM). Graphene sheets grown on copper foil by chemical vapor deposition were transferred to a silicon wafer covered with a 300 nm thick thermal SiO2 layer and then patterned into a grating structure using the standard lithography technique. Raman spectroscopy and SMM were employed to monitor the defect generation and the induced surface impedance change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It is well known that the surface plasmon resonance frequency in GNRs is a function of the width and the carrier density of the ribbons. 348 Although challenging to characterize at the nanoscale, the inactive edge has been evidenced by Raman spectroscopy 349 and microwave atomic force microscopy 350,351 to show different characteristics than in the basal plane. In addition, Fei et al 352 also reported that the carrier density is enhanced near the sample edge using near-eld infrared nanoimaging in exfoliated graphene.…”
Section: One-and Two-dimensional Defects (Topological Defects)mentioning
confidence: 99%
“…It is well known that the surface plasmon resonance frequency in GNRs is a function of the width and the carrier density of the ribbons. 348 Although challenging to characterize at the nanoscale, the inactive edge has been evidenced by Raman spectroscopy 349 and microwave atomic force microscopy 350,351 to show different characteristics than in the basal plane. In addition, Fei et al 352 also reported that the carrier density is enhanced near the sample edge using near-eld infrared nanoimaging in exfoliated graphene.…”
Section: One-and Two-dimensional Defects (Topological Defects)mentioning
confidence: 99%
“…It is postulated by Yan et al that an “inactive” area on the edge of the GNRs about 28 nm wide reduces the width of the effective area in which the plasmons oscillate. The inactive edge, albeit difficult to characterize at the nanoscale, has been evidenced by Raman spectroscopy and microwave atomic force microscopy , to show different characteristics than in the basal plane. In addition to that, Fei and Rodin et al also alluded that in exfoliated graphene, the carrier density is enhanced near the sample edge by using near-field infrared nanoimaging .…”
Section: Introductionmentioning
confidence: 99%